PENGOLAHAN VIRGIN COCONUT OIL PADA MASYARAKAT PEDALAMAN DI DUSUN III SRI PENGANTIN KECAMATAN STL ULU TERAWAS - Ivoni Susanti; Fitria Lestari; Yuli Febrianti; Agus Andriansah; Gusti Aldo Wijaya (Nusantara Hasana Journal, 2023)
Sri Pengantin Hamlet is a hamlet nicknamed "Bamboo Village" by the South Sumatra Provincial Government. Apart from that, another abundant potential in this hamlet is coconut plants. Access to this hamlet can only be reached via water for 45 minutes - 1 hour using a means of transportation called "ketek". Apart from the difficulty of access, the unavailability of electricity and signals means that the lives of the people in this hamlet are still lagging behind compared to other hamlets in the same sub-district. Apart from living, the economy in this hamlet is still quite low with livelihoods only relying on coffee plantations. In fact, the abundance of coconuts should be able to increase the economic income of the people in the village. Therefore, one of the activities carried out is holding training on processing coconut into virgin coconut oil (VCO). The results of the research show that there has been an increase in community skills in processing coconut into VCO from 39 to 92.35% with the proposed business management in the form of storing the VCO produced so that it can be resold so that it can help the community's economy. It is concluded that the abundant natural potential can be processed into valuable products with creativity.